Ungdommen - Ødegård, Guro; Pedersen, Willy (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
How have smart phones and social media changed life for young people today? Why do we get irritated when boys are in trouble, but worried when girls are? How do Muslim youth really feel about being called a 'goddamned terrorist'?YOUTH reveals what it's like to be a young person in today's world. We gain new empirical information on life within the context of family, school, and sports. We are invited to drinking parties where sexual boundaries are tested. We also tag along with a group of guys on a hunting trip where the shotgun shells are high gauge. And: Is it true that rates of anxiety and depression have increased? Or that gender identity has become so fluid that more and more young people believe they are neither 'girl' nor 'boy'?The book details some distinct trends - a school that disciplines students in new ways, less alcohol consumption and problematic behavior, disinclination toward early sex. We also see a fascinating political activism. It is the young who are on the frontlines of the climate crisis battle.Publication of YOUTH also marks the 30th anniversary of the leading center for youth research in Norway, established at NOVA, the Norwegian Social Research institute at Oslo Metropolitan University.This book will be relevant to researchers, students, teachers and all those who work on behalf of young people from the national to the local level, as well as politicians, journalists and others interested in research-based information about how young people actually live today.Guro Ødegård is a senior researcher and institute leader at OsloMet's Norwegian Social Research institute, NOVA. Willy Pedersen is professor of sociology at the University of and a NOVA affiliate.; Hvordan har smarttelefonen og sosiale medier endret livet til dagens unge? Hvorfor irriterer vi oss over gutter som lager trøbbel for andre, mens vi bekymrer oss for jenter som sliter? Hvordan oppleves det egentlig for muslimske ungdommer å bli kalt «jævla terrorist»?UNGDOMMEN bretter ut livet til dagens unge. Vi får ny empirisk kunnskap om livet i familien, i skolen og i idretten. Vi blir med inn på fuktige fester hvor seksuelle grenser presses. Men vi blir også med en gjeng gutter på jakt, hvor haglpatronene skal være av grovt kaliber. Dessuten: Stemmer det at forekomsten av angst og depresjon har økt? Eller at kjønnskategoriene flyter, at stadig flere opplever at de hverken er «gutt» eller «jente»?Boken viser noen tydelige tendenser - en skole som disiplinerer elevene på nye måter, mindre alkohol og problematferd, tilbakeholdenhet med tidlig sex. Samtidig ser vi et fascinerende politisk opprør. Det er ungdom som viser vei i klimakampen.UNGDOMMEN markerer at det er 30 år siden det ledende ungdomsforskningsmiljøet i Norge, som befinner seg på NOVA ved OsloMet, ble etablert.Boken henvender seg til forskere, studenter, lærere og alle som arbeider med ungdom på statlig og lokalt nivå, samt til politikere, journalister og andre som kan ha nytte av forskningsbasert kunnskap om hvordan ungdom faktisk lever i dag.Guro Ødegård er forsker 1 og instituttdirektør ved Velferdsforskningsinstituttet NOVA ved OsloMet. Willy Pedersen er professor i sosiologi ved Universitetet i Oslo og tilknyttet NOVA ved OsloMet.